Literature Review: Early Education of Type 1 Diabetes Mellitus on Children's Health Awareness - Gadis Halizasia; Surahman Tanjung; Dedek Alis Monika; Nurul Ayla; Safira; Rimadeni, Yeni; Lisni , Lisni (Teewan Solutions, 2025)
Type 1 Diabetes Mellitus (T1DM) is a chronic condition that is often diagnosed in childhood and requires long-term management. Early education plays an important role in shaping children's understanding and readiness to face this disease. The purpose of this study was to examine the impact of educational interventions on children's knowledge, attitudes, and abilities in managing T1DM. The review was conducted by analyzing a number of relevant national and international literature, especially those discussing child-based education methods, the role of parents and schools, and the use of digital media and educational games. The results of the review showed that education provided through a personal, interactive, and consistent approach can improve children's understanding of self-care, including recognizing symptoms of hypoglycemia, insulin management, and healthy eating patterns. Active family involvement and collaboration with educational institutions also strengthen the effectiveness of the program. It can be concluded that education that begins early, with a comprehensive and cross-sectoral approach, is very important up to 82% in improving children's readiness to live a healthy life with DMT1. Keywords: Early Education, Type 1 Diabetes Mellitus, Health Awareness, Children.